A high resolution analysis of macroscopic charcoal deposited in peat - Ventorp, David (SLU/Southern Swedish Forest Research Centre, 2007)
The amount of macroscopic charcoal in the top 25 cm of three cores from a peat land in Hornsö Ecopark, south-eastern Sweden, was compared to the dendrochronology inferred fire history of the site. Because of the occurrence of a recent fire ex-situ (1999) and one fire ¬in-situ inferred by three fire scared Scots pines, Pinus sylvestris, adjacent (5-10 m) to the peat cores, the site provided an excellent opportunity to compare the abundance of charcoal deposited in a peat land after fires in-situ and ex-situ. The objectives of the study were threefold: 1) to investigate the relationship between numbers of charcoal fragments (#/cm3) and measured fragment area (mm2/cm3); 2) to test if the smaller size classes could be excluded without changing the signal from the charcoal profile significantly; and 3) to compare the abundance of charcoal deposited between a fire in-situ and ex-situ. The number of charcoal fragments and the measured charcoal area exhibited a highly significant correlation (P < 0.001 in all three peat cores). When comparing the total number of charcoal fragments > 0.28 mm with those > 0.50 mm in diameter the same charcoal peak pattern emerged. The two size classes also showed a highly significant correlation (P < 0.001 in two and P < 0.05 in one of the cores). Even if ambiguity arose concerning which charcoal peak that should represent the fire of 1908, the fire of 1999 did not produce a clear peak in the charcoal profile. It was concluded that the parameter "number of charcoal fragments" is preferred over the measured charcoal area in most cases. Even if the > 0.28 and > 0.50 mm size classes exhibited the same charcoal peak profiles one should be cautious to exclude the 0.28-0.50 mm class. The study suggests that fires in-situ depose more charcoal in the peat stratigraphy than fires ex-situ.